Replacing a combined tax on land and buildings’ with a simplified land value tax’ in the federal republic of Germany - Weiss, Erich (International Journal of Strategic Property Management, 2010)
In early 2004 the finance ministers of Bavaria and Rhineland‐Palatinate put forward a new model for assessing land tax. The model envisages the abolition of the current Land Tax A (tax on agricultural and forestry enterprises); Land Tax B (developed/developable real estate) is in future to comprise a flat‐rate tax on the buildings and a more up‐to‐date and realistic taxation of the land value based on the standard land value. Nevertheless, the question still remains: Why not go one step further and replace this ‘combined tax on land and buildings’ with a simple ‘land value tax'?First Published Online: 18 Oct 2010